Improvement of Specific Multi-target Tracking Algorithm in Cross-domain Environment - MU Xiaofang; LI Hao; LIU Jiaji; LIU Zhenyu; LI Yue (Taiyuan Ligong Daxue xuebao)
[Purposes] Multi-target tracking in the cross-domain environment of surveillance video is a very important and challenging task in intelligent security. The difficulties of this task lie in the frequent occlusion between the objects in video frame, the unknown start and end time of the trajectory, the too small sized targets, the interactions between the objects, the apparent similarity, and the camera angle changes. In view of the frequent occlusions and apparent similar problems, an improved multiple target tracking algorithm is put forward. [Methods] With the maximum use of low detection object, secondary matching is performed on the unmatched low objects. For target cross-domain, camera’s topological sort rules, adjacent cameras un tracking trajectory, as well as the detector YOLOv5 algorithm improvement and the layer-to-layer transfer of information streams, effectively address the multi-scale problems and the unsufficient information extraction problems for small objects, promptly match the tracking objects in adjacent camera, thus improving . the accuracy of multi-target tracking in cross-domain environment. [Findings] In the comparative ablation tests, the MOTA value of the improved algorithm reached 62.8%, and the IDswitch value was also significantly reduced.